Happiness Issue – Moral Aspects of its Biochemical Enhancement - Plašienková, Zlatica; Farbák, Martin (Studia Ecologiae et Bioethicae, 2021)
The search for happiness is something that constitutes human existence from its beginning, and even though people have achieved unimaginable progress in science and technologies, they still have not found the secret of being happy. Transhumanist authors, headed by Mark Walker, believe we can reach happiness biochemically using specific drugs and without considerable side effects. They consider it to be our moral duty because it would increase the prosocial behaviour of people enhanced in that way, following research showing that the happier people are, the more useful it is for society. In this paper, we critically respond to the vision of biochemical enhanced happiness (bio-happiness). We follow the classic and modern authors in our analysis of what happiness is, and based on this analysis, we want to demonstrate why the biochemical enhancement of happiness is not a moral imperative these days. On the contrary, we offer the reasoning why such a vision of bio-happiness is not morally right, and why it bears the risk of losing the connection between happiness and finding the meaningfulness of life. We critically evaluate the absence of spirituality in the transhumanist understanding of man and the devaluation of her/his intrinsic values.